UPAYA MENINGKATKAN KREATIFITAS ANAK MELALUI KEGIATAN MENGGAMBAR - Asma'urrahman, Nailurriza; Riami; Sumiati; Nisail Fitriah, Khoirotun (As-Sulthan Journal of Education, 2024)
The purpose of the study to improve children's creativity through drawing activities every day The type of research used is Class Action Research with the subject of child researcher group B Kindergarten Zainur Ridho as many as 15 people, 8 girls and 7 boys. Data taken through observation, documentation and data analysis techniques with percentages. This study was conducted as many as 2 cycles each cycle consisting of 3 meetings, in cycle I the child's reading ability is still low while in cycle II meeting 3 there is an increase that the child's creativity ability increases very high. The conclusion of the results shows that there is an increase in children's creativity through drawing activities every day.